1983
DOI: 10.1136/bmj.287.6392.575
|View full text |Cite
|
Sign up to set email alerts
|

Spread of rotavirus within families: a community based study.

Abstract: The spread of rotavirus infection was studied over four weeks in a sample of 28 families exposed to a child with rotavirus infection. The results showed a high incidence of intrafamilial infection, with 46% of members of these families developing rotavirus infections compared with none in another series of 18 families. Children in the families with an index case were more frequently affected than adults: 75% of the children developed rotavirus infection but only 33% of the adults.Children tended to suffer the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 9 publications
6
34
1
1
Order By: Relevance
“…The RV seroconversion rate in both type 1 diabetic high-risk and lower-risk groups of children was similar to that generally reported in children (0.8/year) (14). In addition, the rate of concurrent RV infection in the sibling pairs was the same as that (55%) reported for intrafamilial transmission in families without type 1 diabetes (24,26). Thus, at-risk children in these type 1 diabetes families did not appear overall to be infected by RV with increased frequency.…”
Section: Discussionsupporting
confidence: 56%
“…The RV seroconversion rate in both type 1 diabetic high-risk and lower-risk groups of children was similar to that generally reported in children (0.8/year) (14). In addition, the rate of concurrent RV infection in the sibling pairs was the same as that (55%) reported for intrafamilial transmission in families without type 1 diabetes (24,26). Thus, at-risk children in these type 1 diabetes families did not appear overall to be infected by RV with increased frequency.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, we did not include asymptomatic and mild cases in our calculation of the infection-rate parameter. The majority of household transmission studies have suggested that symptomatic individuals are more infectious and important in transmission than incubating or asymptomatically infected individuals (Haug et al 1978;Rodriguez et al 1979;Grimwood et al 1983;Banerjee et al 2008). Therefore, we feel that not accounting for asymptomatic and mild cases in our calculation of the infection-rate parameter was justified.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we consider the case in which individuals can be infected due to external sources, which is an addition to the classic SIR setting. We provide here efficient procedures to analyse conveniently defined stochastic descriptors for the epidemic spread, being applicable in the relevant situation where N is small, which is the case in problems such as the epidemic spread throughout the members of a family [9,17] or among the patients within an intensive care unit [4,11,14,28]. Although results developed in this paper are, theoretically, valid regardless the value of N , the computational nature of our procedures makes unfeasible their application once N exceeds small values (see Section 5 and Appendix C), and their interest beyond these values should be considered strictly mathematical.…”
Section: Introductionmentioning
confidence: 99%